The Saposin-Like Protein AplD Displays Pore-Forming Activity and Participates in Defense Against Bacterial Infection During a Multicellular Stage of Dictyostelium discoideum - Dhakshinamoorthy, Ranjani; Bitzhenner, Moritz; Cosson, Pierre; Soldati, Thierry; Leippe, Matthias (Frontiers in Cellular and Infection Microbiology, 2018)
Due to their archaic life style and microbivor behavior, amoebae may represent a source of antimicrobial peptides and proteins. The amoebic protozoon Dictyostelium discoideum has been a model organism in cell biology for decades and has recently also been used for research on host-pathogen interactions and the evolution of innate immunity. In the genome of D. discoideum, genes can be identified that potentially allow the synthesis of a variety of antimicrobial proteins. However, at the protein level only very few antimicrobial proteins have been characterized that may interact directly with bacteria and help in fighting infection of D. discoideum with potential pathogens. Here, we focus on a large group of gene products that structurally belong to the saposin-like protein (SAPLIP) family and which members we named provisionally Apls (amoebapore-like peptides) according to their similarity to a comprehensively studied antimicrobial and cytotoxic pore-forming protein of the protozoan parasite Entamoeba histolytica. We focused on AplD because it is the only Apl gene that is reported to be primarily transcribed further during the multicellular stages such as the mobile slug stage. Upon knock-out (KO) of the gene, aplD− slugs became highly vulnerable to virulent Klebsiella pneumoniae. AplD− slugs harbored bacterial clumps in their interior and were unable to slough off the pathogen in their slime sheath. Re-expression of AplD in aplD− slugs rescued the susceptibility toward K. pneumoniae. The purified recombinant protein rAplD formed pores in liposomes and was also capable of permeabilizing the membrane of live Bacillus megaterium. We propose that the multifarious Apl family of D. discoideum comprises antimicrobial effector polypeptides that are instrumental to interact with bacteria and their phospholipid membranes. The variety of its members would allow a complementary and synergistic action against a variety of microbes, which the amoeba encounters in its environment.